(untitled) (Texas Journal of Medical Science, 2024)
In this article, researches were conducted on the morphological and morphometric indicators of intrapulmonary bronchus vascular wall tissues. The structures of the respiratory bronchioles of babies during the first childhood were studied. During the study, the following was proven: the layers of the respiratory bronchioles of young children between the ages of 4 and 7 are not well developed; the covering epithelium is multi-layered and single-layered, from the transformation of the connective tissue from the unformed. It was found that connective tissue-forming tissue, sparse chondroid and dense chondromatous tissue is covered with small cells